Color effects in print advertising: A research update (1985-2012) - Panigyrakis, George G.; Kyrousi, Antigone G. (My University, 2015)
Purpose – The purpose of this paper is to review the literature published since 1985 regarding color effects in advertising and at setting an agenda for future research. Design/methodology/approach – Recent publications (1985-2012) regarding the effects of color in advertising on consumers’ attention, memory and emotional responses are reviewed and discussed. Findings – The review reveals that the effects of color on attention, emotion and memory still remain largely unknown, mainly due to the inherent complexity of the subject and lack of systematic research. At the same time, promising research venues and challenges for the future are identified in the form of research questions. Originality/value – The key potential contribution of this paper stems from the identification of promising research questions and challenges for investigating the role of color in advertising.
Keywords: Advertising; Attention; Color; Emotion; Memory